Gestión de las vías de participación en el ciberperiodismo - López García, Xosé (Estudios sobre el Mensaje Periodístico, 2007)
Different tools of recent appearance have multiplied user ways of participation, especially in phases that are previous to informative message construction. This fact is an important step to consolidate citizenship ways of access and intervention, but, at the same time, increases the risk of non-contrasted information and no news. This fact involves an important step to the creation of citizens’ ways of access and intervention, but may also increase risks to the practice of Quality Journalism. Therefore, control systems are needed to guarantee information veracity. In short, citizens’ participation on media must be ensured, but there must be clear and guaranteed ways of access for traditional media and and cybermedia.